Zaakwaarneming dalam Teori dan Praktek Kontemporer - Faisal Luqman Hakim (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Basically, human beings can not live alone. Knowingly or not humans always require the presence of other humans. The existence of a sense of mutuality between humans leads to the interaction between other people. Interaction that led to acts of human relations in society. That there is a prohibited act and there are allowed by law. In the Civil Code is set on the action as a result of human interaction is allowed. The act is called zaakwaarneming. Zaakwaarneming is the act of taking care of other people's business that done voluntarily. While still an undergraduate studies, I often get an understanding of the examples of acts that can be categorized as zaakwaarneming. And when I read some posts on the internet media and books, examples of the action zaakwaarneming also provided a similar example. And without us knowing it, if attention to the elements of the act which can be categorized as zaakwaarneming, some actions are still many in society who can be categorized as such actions. Among the acts that can be categorized as zaakwaarneming are an accident working, caring for the sick, helping traffic accident victim, helping a lost child, and find the property of others.